The Habits of Effectiveness of the Muslim Personality in the Light of Al-Nawawi's Forty Hadiths - Al-Shurman , Khaled (Dirasat: Shari'a and Law Sciences, 2020)
The research deals with the issue of effective personality habits that were mentioned in the forty hadiths of Al-Nawawi by clarifying the meaning of the habits of agency, extract the principles and values ​​that contribute to building the habits of agency from the forty hadiths of Al-Nawawi and to deduce their impact on the personality of a Muslim. The research adopted the analytical method to extract all the principles contained in forty hadiths of Al-Nawawi and classified them into a special table, also extracted all the values, all the behaviors that form habits, and reassembled them to reach the results. The research found the following. The first is defining the habits of effectiveness as the habits that increase achievement and make the Muslim live in balance. The study confirmed the richness of the content of the forty hadiths of Al-Nawawi in the ability to form the habits of effectiveness of the Muslim, and that they contain essential principles suitable for managing the life of a Muslim. The effect resulting from the application of the principles and values ​​contained in the hadiths contributes to the formation of an effective personality in all aspects of life. The study recommended deepening the study of the elements that constitute Muslim effectiveness in terms of principles, values, behaviors and results, and developing new practical mechanisms and strategies derived from the Qur’an, Sunnah and successful human experiences of teaching the forty hadiths of Al-Nawawi with the aim of building habits of effectiveness in the Muslim.